2018
DOI: 10.1111/josh.12627
|View full text |Cite
|
Sign up to set email alerts
|

Formative Research to Create a Farm‐to‐School Program for High School Students in a Lower Income, Diverse, Urban Community

Abstract: These findings provide theory-based strategies for how to promote local produce consumption among a diverse group of urban high schools students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Twelve studies were conducted in the United States (US) [ 37 , 39 – 47 , 50 , 51 ], two in Europe [ 48 , 49 ], one in Australia [ 52 ] and another one in New Zealand [ 38 ]. Eight studies included a range of ethnic groups [ 37 – 40 , 42 , 44 , 50 , 51 ], three studies exclusively focused on African American populations [ 41 , 46 , 47 ], one study [ 43 ] targeted Asian American people including Chinese, Vietnamese and Hmong participants, and one study [ 45 ] exclusively focused on Hmong (Southeast Asian origin) participants. Three manuscripts [ 48 , 49 , 52 ] did not provide details about race/ethnicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies were conducted in the United States (US) [ 37 , 39 – 47 , 50 , 51 ], two in Europe [ 48 , 49 ], one in Australia [ 52 ] and another one in New Zealand [ 38 ]. Eight studies included a range of ethnic groups [ 37 – 40 , 42 , 44 , 50 , 51 ], three studies exclusively focused on African American populations [ 41 , 46 , 47 ], one study [ 43 ] targeted Asian American people including Chinese, Vietnamese and Hmong participants, and one study [ 45 ] exclusively focused on Hmong (Southeast Asian origin) participants. Three manuscripts [ 48 , 49 , 52 ] did not provide details about race/ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…Interviews data were analyzed using content analysis and coding techniques Gerritsen, 2019 [ 38 ] Fruit and vegetable intake Community-based: 17 students, parents,teachers, community leaders, local retailers, and health promoters Sex: mixed Age: 16-25 years Race/ethnicity: Maori, Pacific, Asian and New Zealand European Setting: neighborhood community Country: New Zealand Three group model building workshops with all participants together No information Structured system dynamics method to create a causal loop diagram Goh, 2009 [ 42 ] Healthy eating (and physical activity) School- based (2 schools): 119 adolescents, 63 parents, and 28 community stakeholders Sex: mixed Age: mean 12 years (7th-8th graders) Race/ethnicity: 58% Latino Setting: middle school Country: US FG discussions: 6 male teenagers FGs, 8 female teenagers FGs, 8 parent FGs. 28 interviews with community stakeholders No information No information Greer, 2018 [ 50 ] Local produce consumption School-based (3 schools): 53 students Sex: mixed Age: no information Race/ethnicity: non-Hispanic black, Hispanic, non-Hispanic white and Asian Setting: public high schools Country: US 6 students FGs (2 FGs per school) Social cognitive theory No information Harrison, 2005 [ 43 ] Dietary habits, attitudes and knowledge Community-based: 236 participants (15 key informants, 116 parents, and 105 youth participants) Sex: no info Age: 11-14 years Race/ethnicity: Asian American (Chinese, Vietnamese, and Hmong) Setting: community-based organizations Country: US 24 youth and parents FGs 15 interviews with key informants No information Simple thematic content analysis was used to summarize the data by ethnic group and across groups Kubik, 2005 [ 44 ] Dietary practice (and physical activity) School-based (7 alternate...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous Farm‐to‐School research has indicated that hands‐on, food‐based classroom and garden nutrition education effectively increases students' fruit and vegetable knowledge, attitudes/beliefs, exposure, self‐efficacy, willingness to try, preference, and consumption 10,29‐33 . However, exposure to the local messaging 34 and the local vegetables may also affect these behaviors.…”
Section: Discussionmentioning
confidence: 99%